2017
DOI: 10.1080/00498254.2017.1288280
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma metabolic profiles of benzydamine, a flavin-containing monooxygenase probe substrate, simulated with pharmacokinetic data from control and humanized-liver mice

Abstract: 1. Benzydamine is used clinically as a nonsteroidal anti-inflammatory drug in oral rinses and is employed in preclinical research as a flavin-containing monooxygenase (FMO) probe substrate. In this study, plasma concentrations of benzydamine and its primary N-oxide and N-demethylated metabolites were investigated in control TK-NOG mice, in humanized-liver mice, and in mice whose liver cells had been ablated with ganciclovir. 2. Following oral administration of benzydamine (10 mg/kg) in humanized-liver TK-NOG m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To establish a simplified human PBPK model, the human values for k a , V 1 , and CL h , int , as shown in Table , were estimated by employing a scale-up strategy from HL-mice to humans. A multiplicative factor of 0.744 was applied to the rodent k a value to obtain the human k a value. V 1, human was derived using the reported equation based on data from rats, dogs, and monkeys and using fixed values of the human liver volume ( V h , human , 1.50 L) and blood volume ( V b , human , 4.90 L). , The in vivo hepatic intrinsic clearance ( CL h , int ) in humans was estimated based on that of HL-mice, with no consideration for interspecies factors, as previously described: ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish a simplified human PBPK model, the human values for k a , V 1 , and CL h , int , as shown in Table , were estimated by employing a scale-up strategy from HL-mice to humans. A multiplicative factor of 0.744 was applied to the rodent k a value to obtain the human k a value. V 1, human was derived using the reported equation based on data from rats, dogs, and monkeys and using fixed values of the human liver volume ( V h , human , 1.50 L) and blood volume ( V b , human , 4.90 L). , The in vivo hepatic intrinsic clearance ( CL h , int ) in humans was estimated based on that of HL-mice, with no consideration for interspecies factors, as previously described: ,, …”
Section: Methodsmentioning
confidence: 99%
“…21−25 V 1,human was derived using the reported equation 25 based on data from rats, dogs, and monkeys 26 and using fixed values of the human liver volume (V h,human , 1.50 L) and blood volume (V b,human , 4.90 L). 27,28 The in vivo hepatic intrinsic clearance (CL h,int ) in humans was estimated based on that of HL-mice, with no consideration for interspecies factors, as previously described: 18,24,29 A system of differential equations, as described above, was also solved to model the concentrations in each compartment in humans. Forward and reverse dosimetry was conducted using this human PBPK model for DBP/MBP.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…83) Human PK prediction methods based on PBPK models using chimeric mice with humanized liver have been also reported. Utoh et al 84) reported the suitable predictability of human plasma concentration profiles of CYP probes based on a simplified PBPK model consisting of three compartments using humanized liver TK-NOG mice. However, Yamazaki-Nishioka et al 85) reported the overprediction of human CL h for benzydamine, a FMO substrate, based on a simplified PBPK model using humanized liver TK-NOG mice, as was also reported by Miyamoto et al 82) They suggested that the failure of prediction might be due to the effect of oxidation in the kidney, extra-hepatic metabolism.…”
Section: Prediction Of Human Pk Using Chime-ric Mice With Humanized Lmentioning
confidence: 99%
“…6(B)). 82,84,86) As described above, drug metabolism by residual mouse hepatocytes in the liver of chimeric mice with humanized liver affects the predictability of human PK. To improve predictability, correction methods using CL int, in vitro in humans and animals have been reported.…”
Section: Prediction Of Human Pk Using Chime-ric Mice With Humanized Lmentioning
confidence: 99%
“…2013; Bateman et al, 2014;Kamimura et al, 2015;Nakada et al, 2016;Wilson et al, 2018); drug-drug interaction (Hasegawa et al, 2012;Nishimura et al, 2013;Yamazaki et al, 2013;Suzuki et al, 2017;Uchida et al, 2018); human pharmacogenetic studies (Hu et al, 2013;Nishiyama et al, 2015); or other DME studies Inoue et al, 2009;Sanoh et al, 2012aSanoh et al, , 2015Schulz-Utermoehl et al, 2012;Tsukada et al, 2013;Suemizu et al, 2014;Nishiyama et al, 2015;Utoh et al, 2016;Kamimura et al, 2017;Shimizu et al, 2017;Yamazaki-Nishioka et al, 2018). A detailed analysis of all these studies is beyond the scope of this review; we will confine our review to a few examples illustrating the utility of human liver chimeric mice for drug studies.…”
Section: Downloaded Frommentioning
confidence: 99%